Immediate Effects of Smoking on Cardiorespiratory Responses During Dynamic Exercise: Arm Vs. Leg Ergometry - Chen, Chien-Liang; Tang, Jing-Shia; Li, Ping-Chia; Chou, Pi-Ling (Frontiers in Physiology, 2015)
Purpose: This study compared the immediate effects of smoking on cardiorespiratory responses to dynamic arm and leg exercises. Methods: This randomized crossover study recruited 14 college students. Each participant underwent 2 sets of arm-cranking (AC) and leg-cycling (LC) exercise tests. The testing sequences of the control trial (participants refrained from smoking for 8 hours before testing) and the experimental trial (participants smoked 2 cigarettes) were randomly chosen. We observed immediate changes in pulmonary function and heart rate variability after smoking and before the exercise test. The participants then underwent graded exercise tests of their arms and legs, respectively, until reaching exhaustion. We compared the peak work achieved and the time to exhaustion during the exercise tests with various cardiorespiratory indices [i.e., heart rate, oxygen consumption (VO2), minute ventilation (VE)]. The main effects of the time and the trial, as well as their interaction effects on outcome measures, were investigated using repeated measure ANOVA. Results: Five minutes after smoking, the participants exhibited reduced forced vital capacities and forced expiratory volumes in the first second (P < .05), in addition to elevated resting heart rates (P < .001). The high-frequency, low-frequency, and the total power of the heart rate variability were also reduced (P < .05) at rest. For the exercise test periods, smoking reduced the time to exhaustion (P = .005) and the ventilatory threshold (P < .05) in the LC tests, whereas there were no significant effects in the AC tests. A trend analysis revealed a significant (P < .001) trial-by-time interaction effect for heart rate, VO2, and VE during the graded exercise test. Lower VO2 and VE levels were exhibited in the exercise response of the smoking trial than in that of the control LC trials, whereas there was no discernable inter-trial difference in the AC trials. Moreover, the differences in heart rate and VE response between the LC and AC exercises were significantly smaller after the participants smoked. Conclusion: This study verified that smoking can significantly decrease performance and cardiorespiratory responses to leg exercises. However, the negative effects of smoking on arm exercise performance were not as pronounced.